The Influence Of Mind Mapping Learning Model With Canva Media To Student’s Cognitive Learning Results On Social Studies Subject At Smpn 3 Cimahi - Anisa, Ulfah (Universitas Pendidikan Indonesia (UPI), 2023)
This research is based on the reality of using the Mind Mapping Learning Model with Canva media. Social studies education develops learning that requires the use of technology in accordance with current developments. Therefore, it is necessary to integrate learning using the mind mapping learning model with Canva media on students' cognitive learning results. This research aims to determine the influence of learning using the mind mapping learning model with Canva media on students' cognitive learning result at SMPN 3 Cimahi. This research approach uses a mix method or combination research method. Data collection was carried out through observation, interviews, question and documentation studies. Data analysis techniques use descriptive qualitative data and descriptive statistics, normality tests, hypotheses, validity tests and reliability tests. The findings of this research are: 1) There is an influence on planning on students' cognitive learning outcomes using the mind mapping learning model with Canva media 2) There is an influence between learning management and student learning results using the Mind Mapping learning model with Canva media 3) There is no influence between problem learning with student learning results. The results of this research recommend that the mind mapping learning model using Canva media can be developed as adequate learning media for making mind maps and frequently practicing using the features in Canva.